Longer-term economic impacts of self-help groups in India - Deininger, Klaus W. 1962- (World Bank, 2009)
"Despite the popularity and unique nature of women's self-help groups in India, evidence of their economic impacts is scant. Based on two rounds of a 2,400 household panel, the authors use double differences, propensity score matching, and pipeline comparison to assess economic impacts of longer (2.5-3 years) exposure of a program that promoted and strengthened self-help programs in Andhra Pradesh in India. The analysis finds that longer program exposure has positive impacts on consumption, nutritional intake, and asset accumulation. Investigating heterogeneity of the impacts suggests that even the poorest households were able to benefit from the program. Furthermore, overall benefits would exceed program cost by a significant margin even under conservative assumptions. "--World Bank web site
Includes bibliographical references. - Title from PDF file as viewed on 5/7/2009
Keywords: Self-help groups -- India -- Andhra Pradesh